2014
DOI: 10.1016/j.jcyt.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and financial burden of pre-emptive management of cytomegalovirus disease after allogeneic stem cell transplantation—implications for preventative treatment approaches

Abstract: Background Although CMV infection after allogeneic stem cell transplantation (SCT) is only rarely fatal, the management of CMV by preemptive medication for viral reactivation has toxicity and carries a financial burden. New strategies to prevent CMV reactivation with vaccines and antiviral T cells may represent an advance over preemptive strategies, but have yet to be justified in terms of transplant outcome and cost. Patients and methods We compared outcomes and post-transplant treatment cost in 44 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 46 publications
7
50
0
2
Order By: Relevance
“…Our case study thus demonstrates that immunotherapy may offer not only significant clinical advantages to immunocompromised patients, but can also be manufactured at a reasonable cost if an appropriate operational model is adopted. Our findings also mirror results from other studies examining the need to reduce the economic burden of post-transplantation care (9,30).…”
Section: A Case Study: Cmv-specific T Cells For Adoptive Immunotherapysupporting
confidence: 88%
See 1 more Smart Citation
“…Our case study thus demonstrates that immunotherapy may offer not only significant clinical advantages to immunocompromised patients, but can also be manufactured at a reasonable cost if an appropriate operational model is adopted. Our findings also mirror results from other studies examining the need to reduce the economic burden of post-transplantation care (9,30).…”
Section: A Case Study: Cmv-specific T Cells For Adoptive Immunotherapysupporting
confidence: 88%
“…Thus, adoptive immunotherapies associated with lower toxicities for the prevention and treatment of CMV infection and disease are highly needed and may also produce overall cost savings in posttransplant patient care. Indeed, a recent study has suggested that even if the prevention capabilities of antiviral donor-derived cytotoxic T lymphocytes (CTL) in HSCT, which cost $10,000 to manufacture, would only be 50% effective at avoiding the need for antiviral treatment, it is still considered the less expensive option compared to the cost of antiviral treatment and associated hospital care of more than $50,000 per patient (9). Researchers working in this field anticipate that such therapies could replace conventional treatments, possibly allowing this novel therapeutic category to be accepted as standard practice (10).…”
mentioning
confidence: 99%
“…Adoptive cellular immunotherapy, after having amassed an excellent record for efficacy and safety, is advancing from therapy of refractory disease to prophylaxis. Boosting immune reconstitution and antiviral immunity post (CB) HCT rather than focusing on pharmacotherapy has the potential to be cost effective 3335 . Regardless of the approach, our data confirms that there is a great scope for further improving the management of CMV after cord blood HCT.…”
Section: Discussionmentioning
confidence: 99%
“…The management of CMV viraemia is further complicated by potential treatment toxicities (e.g. ganciclovir‐induced neutropenia, nephrotoxicity), prolonged hospitalisation, worse ICU outcomes, increased risk for other bacterial or fungal infections, increased healthcare costs and contribution to transplant‐related mortality . Overall, it is estimated that the attributable healthcare cost of managing CMV is US$58 000–74 000 per patient, placing a large economic burden on over stretched healthcare resources …”
Section: Burden Of CMV Viraemiamentioning
confidence: 99%